Philosophical and epistemological concept of scientific methods of knowledge and their pedagogical reflection (Pedagogy of Higher and Secondary Education, 2012)
Polishchuk H. P. Philosophical and epistemological concept of scientific methods of knowledge and their pedagogical reflection.The article reviews the common approaches to the method as a scientific concept in the structure of cognitive process. The emergence of scientifically based methods knowledge (a methodology as a system of principles and methods of organizing and building a theoretical and practical activities) – is the result of creative achievements of thinkers of different times, eras, nations. Their product is the nature of the method, its basis, functions
Keywords: method; methodology; instruction; cognitive process; subject of cognition; object of cognition; dialectics